Zhichang Zui zhongyao de Xiaoshi = Important Little Things In The Office - Xie, Wenxian (Beijing, China: Beijing Times Chinese Bookstore, 2019)
This book describes how to overcome the stereotypes of newcomers in the workplace, how to manage the interpersonal relationship between supervisors and colleagues, and how to combine work with interests.
In Chinese.
Keywords: Employee training personnel; Career choices -- popular books